Correlation between production parameters and mechanical properties of ABS plus p430 fused deposition material. (March 2022) - Corsi, M; Bagassi, S; Moruzzi, MC; Seccia, L
Fused Deposition Modeling (FDM), is one of the most popular and widely used Additive Manufacturing filament based technology employing materials such as Acrylonitrile Butadiene Styrene (ABS), Polycarbonate (PC), Thermoplastic Polyurethane (TPU) and Polylactic Acid (PLA). In this technique, the part is built up layer-by-layer, affecting, both the resolution along the z-axis, and the mechanical properties dependent on the mesostructure, controlled by a large amount of production parameters such as layer thickness, raster orientation, number of contour and air gap. When dealing with functional and structural printed parts, a deep understanding of these tunable building parameters and their influence on the mechanical properties is of the utmost importance and over the years many experimental studies have been carried to investigate this need. This study is intended to explore specimens realized through FDM technique with different combinations of printing parameters to analyse their effect on the mechanical properties of ABS Plus p430. To this aim, tensile and compression specimens, had been designed and tested. Sixteen different types of tensile specimen had been realized by varying four different parameters, namely, layer thickness, part interior style, infill orientation and number of contours. Whereas, the number of compression specimens had been limited to four considering the variation of two parameters: layer thickness and part interior style. Three samples for each specimen had been produced in ABS Plus p430 using a Stratasys Fortus 250mc FDM printer and tested with a universal testing machine through tension and compression tests to analyse the correlation between printing parameters and material properties. Test results had led to important conclusions on the consistency and homogeneity of the mechanical properties and on the variation of the material's performances in accordance with the different combinations of production parameters.